ŚWIADOMOŚĆ PODRĘCZNIKOWA NAUCZYCIELA. TEORETYCZNE RAMY OPISU - Andrzejewska, Ewa (Neofilolog, 2019)
The following article aims to explain the concept of textbook awareness that in foreign language teaching literature is used to denote an element of teacher’s professional competence. The underpinnings of this concept are based on an analysis of its definition as postulated by Koenig (2010) and a critical survey of subject literature on the teacher-textbook relationship. This article shows how the concept of text-book awareness is justified and can be implemented. The significance of the role of textbook awareness in teacher’s didactic practice and professional development is highlighted.